Neuropeptide Y Y2 antagonist treated ovariectomized mice exhibit greater bone mineral density. (February 2018) - Seldeen, K.L.; Halley, P.G.; Volmar, C.H.; Rodríguez, M.A.; Hernandez, M.; Pang, M.; Carlsson, S.K.; Suva, L.J.; Wahlestedt, C.; Troen, B.R.; Brothers, S.P.
Abstract: Osteoporosis, a disease characterized by progressive bone loss and increased risk of fracture, often results from menopausal loss of estrogen in women. Neuropeptide Y has been shown to negatively regulate bone formation, with amygdala specific deletion of the Y2 receptor resulting in increased bone mass in mice. In this study, ovariectomized (OVX) mice were injected once daily with JNJ-31020028, a brain penetrant Y2 receptor small molecule antagonist to determine the effects on bone formation. Antagonist treated mice had reduced weight and showed increased whole-body bone mineral density compared to vehicle-injected mice. Micro computerized tomography (micro-CT) demonstrated increased vertebral trabecular bone volume, connectivity density and trabecular thickness. Femoral micro-CT analysis revealed increased bone volume within trabecular regions and greater trabecular number, without significant difference in other parameters or within cortical regions. A decrease was seen in serum P1NP, a measure used to confirm positive treatment outcomes in bisphosphonate treated patients. C-terminal telopeptide 1 (CTX-1), a blood biomarker of bone resorption, was decreased in treated animals. The higher bone mineral density observed following Y2 antagonist treatment, as determined by whole-body DEXA scanning, is indicative of either enhanced mineralization or reduced bone loss. Additionally, our findings that ex vivo treatment of bone marrow cells with the Y2 antagonist did not affect osteoblast and osteoclast formation suggests the inhibitor is not affecting these cells directly, and suggests a central role for compound action in this system. Our results support the involvement of Y2R signalling in bone metabolism and give credence to the hypothesis that selective pharmacological manipulation of Y2R may provide anabolic benefits for treating osteoporosis. Highlights: Treatment with a selective Y2 antagonist increased bone mineral density and trabecular bone volume in ovariectomized mice. NPY Y2 antagonist treatment lowered serum P1NP, a marker used to assess bone formation in bisphosphonate treated patients. Treated mice exhibited higher bone turnover ex vivo, suggesting treatment primes cells for greater response to stimuli. Bone marrow cells from untreated mice did not respond to the Y2 antagonist in vitro, suggesting a central mechanism. These studies suggest some potential for Y2 receptor antagonists to be useful in addressing bone diseases in menopause.